Boston Marathon Mental Health Response Focused on Early Intervention and Resilience - Rizzo, Toni (MD Conference Express, 2015)
Disaster mental health is a well-defined role in emergency preparedness and disaster response. Psychiatric mental health (PMH) nurses are critical members of the disaster response workforce. This article discusses the role of PMH nurses in the response to the 2013 Boston Marathon bombings.